Analysis of polarization of dipole modes in non-circular boreholes in anisotropic formation - G. S. Shchelik (Известия высших учебных заведений: Геология и разведка)
The problem of determination of principle axes in anisotropic formation in non-circular boreholes is studied with numerical simulation of acoustic logging measurements. The processing algorithms for acoustic logging data used in practice involve propagation of two orthogonally polarized waves along borehole axis that correspond to dipole modes. However, the oscillation directions of dipole modes in elliptical boreholes are shown to be substantially non-orthogonal and depend on frequency spectrum of the source signal. This leads to incorrect determination of principle directions in the considered transversely-isotropic media. The results for principle directions obtained after processing are compared with eigenvectors for dipole modes calculated independently with semi-analytical finite element method (SAFE). The application of frequency filters and «non-orthogonal» processing algorithms is proved to be effective for validation and accuracy improvement of the obtained directions.